Factors influencing consumers’ green purchase behavior for sustainable organic food by Botswana university students - Zhou, Noel (International Journal of Scientific Research and Management (IJSRM), 2024)
Sustainability issues are increasingly becoming important in business and society with many businesses in the food sector adopting green organic food production. The understanding of factors influencing consumers' green purchasing behavior will be more important to food marketers. The purpose of this study was to investigate the factors influencing consumers' green purchasing behavior for sustainable organic food by Botswana university students. To achieve this purpose the study followed an investigative qualitative approach. In-depth interviews were used to gather data. A sample of 15 university students was selected using a purposive sampling method. A thematic and narrative analysis method was used for this study. Results show that the factors influencing university students' green purchasing behavior for organic foodstuffs are multi-faceted. These factors include selection criteria such as price. distribution, product performance, and health attributes), consumers' environmental consciousness (environmental awareness, environmental knowledge), and consumers' green attitudes. The practical implications are that the businesses involved in organic food need to intensify the promotion and education of consumers on green and sustainable organic foods. The focus should be on the impact of green products on society, people, and the environment.